Meta Analisis : Pengaruh Pemanfaatan Teknologi Komputer dalam Meningkatkan Hasil Belajar - Maiyana, Efmi; Ambiyar, Ambiyar; Supratman, Supratman (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
Along with the advancement of information technology, the use of computer technology in education has become a subject of increasing attention. The large number of articles that conduct studies on the same field of science may produce different conclusions in their studies, especially in seeing the effect of using computer technology on improving learning outcomes, for this reason a study is needed to analyze this effect. We collected and analyzed information from various relevant studies over the past few years from 2020 to 2023, totaling 16 articles from various sources. This meta-analysis involves research conducted in various contexts of using computer technology in the learning process at various levels of education, with the criteria of the article having an experimental class and a control class, having data such as the number of samples, mean and standard deviation so that the effect size value can be obtained. This research uses quantitative methods by utilizing openmee software as an effect size measure. The results of the analysis show that the utilization of computer technology significantly improves student learning outcomes. This was found in a variety of subjects and education levels, from elementary school to college. In addition, the average effect size results show that it is in the medium category, which means that the use of computer technology in learning affects learning outcomes